Odpowiedzi

Najlepsza Odpowiedź!
2010-02-18T19:17:10+01:00
D) 3x - 3y + 3 = 0
x + 1/2y - 2 = 0

3x - 3y + 3 = 0
x = 2 - 1/2y

6 - 3/2y - 3y + 3 = 0 /*2
x = 2 - 1/2y

9y = 18 /:2
x = 2 - 1/2y

x = 1
y = 2

e) 4x - 2y = 6 /:2
3x + 6y = 12 /:3

2x - y = 3
x = 4 - 2y

8 - 4y - y = 3
x = 4 - 2y

x = 2
y = 1

f) 3x - 4y = 14
-2x + 7y = 18 /:(-2)

3x - 4y = 14
x = 3,5y - 9

10,5y - 27 - 4y = 14 /*2
x = 3,5y - 9

13y = 26
x = 3,5y - 9

x = -2
y = 2

x/3 + y/2 = 1 /*6
x - y = 6

2x + 3y = 6
x = 6 + y

12 + 2y + 3y = 6
x = 6 + y

5y = -6
x = 6 + y

y = -6/5
x = 24/5

b) 2x + y = 6
x/4 - y/5 = 4 /*20

y = 6 - 2x
5x - 4y = 80

y = 6 - 2x
5x - 6 + 8x = 80

y = 6 - 2x
13x = 86

x = 86/13 = 6 8/13
y = -7 3/16

pzdr ;)